"Fiddler crab-type" imidazolium salt as remote substituents tuning organocatalyst for the cycloaddition of epoxides with carbon dioxide. (December 2016) - Chen, Fei; Chen, Dengtai; Shi, Lei; Liu, Ning; Dai, Bin
Graphical abstract: Highlights: "Fiddler crab-type" imidazolium salt were synthesized for the cycloaddition of epoxides with CO2 . They are active for epoxides even with the more hindered substrates. The catalytic performance considerably depends on the remote structural substituents bearing pyridine ring. Abstract: A series of unsymmetrical pyridine-bridged pincer-type imidazolium salts are synthesized and demonstrated as highly active catalyst. This catalyst is for the cycloaddition of carbon dioxide with a broad range of terminal epoxides without organic solvent, and co-catalyst. The performance of catalyst considerably depends on the remote structural feature bearing pyridine ring. In addition, bulky internal epoxide is efficiently converted to the desired product. The robustness of the catalytic system is shown by recycling the catalyst over seven consecutive times without significant loss of activity.